Phase‐specific health system costs of dementia in Ontario, Canada: A propensity score‐matched cohort study. (31st December 2021) - Bronskill, Susan E; Maclagan, Laura C; Mondor, Luke; Fu, Longdi; Guan, Jun; Sewell, Isabella J; Iaboni, Andrea; Wodchis, Walter P; Swartz, Richard H; Maxwell, Colleen J; de Oliveira, Claire
Abstract: Background: Due to increases in the prevalence of dementia across Canada, the economic burden of dementia on provincial health systems is expected to rise. A better understanding of the phase‐specific costs of dementia care, such as periods immediately prior to and following diagnosis as well as other critical points in the life course are needed to support capacity planning. We estimated the phase‐specific costs of dementia over time among older adults and by sex. Method: We identified a cohort of 164, 640 Ontario residents aged 66+ years, ascertained with incident dementia and residing in the community between April 1 st, 2010 and March 31 st, 2017. Controls, who had no previous dementia diagnosis, were 1:1 propensity‐score matched to persons with dementia and individuals were followed to death or study end (March 31 st, 2018). Costs included inpatient care, emergency department care, ambulatory care, home care, long‐term care, physician and healthcare professional services, and prescription drugs. Phase‐based costing methodology examined mean net costs of dementia care throughout four phases of disease progression (pre‐diagnosis, initial, continuing, terminal) and 5‐year net costs. Result: Persons with dementia and matched controls (mean age 81.3 years; 58.7% female) were followed for an average of 3.2 years. Mean net costs of dementia were highest in the terminal phase (32, 679), followed by the initial (17, 656) and continuing phases (13, 423). Higher costs in the dementia group in the terminal phase were driven by acute care (net cost: 16, 324, 95% CI [15, 478, 17, 170]) and long‐term care (14, 006, 95% CI [13, 848, 14, 164]). Net home care costs were highest in the initial phase (1, 839, 95% CI [1, 796, 1, 882]). The net 5‐year cost of dementia was 48, 077 (95% CI [47, 183, 48, 970]; women had higher 5‐year net costs than men (50, 158, 95% CI [49, 053, 51, 263] vs. 44, 800, 95% CI [43, 323, 46, 277]). Conclusion: Observed higher net costs of dementia in specific phases (terminal) and sectors (acute care, long‐term care, home care) highlight where to target interventions to optimize healthcare use and costs that respects quality of life for older adults with dementia and their family care providers.